Human Arenas An Interdisciplinary Journal of Psychology, Culture, and Meaning - Marsico, Giuseppina; Tateo, Luca.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The aim of this journal concerns the interdisciplinary study of higher psychological functions (as topic of a general theory of psyche from the perspective of cultural psychology) in human goal-oriented liminal phenomena in ordinary and extraordinary life conditions. The journal is organized around topics and arenas of human activity, rather than the traditional boundaries of academic disciplines. It will explore human arenas from the point of view of historical foundations, methodology, epistemology, and the intersection of disciplines. Human Arenas promotes an innovative mix of theoretical and empirical studies, as well as qualitative and quantitative approaches based on (3z(Bsmall data,(3y (Bthat is, the analysis of crucial and meaningful data, rather than the inductive accumulation of large empirical (3z(Bevidence.(3y(B.s
Keywords: Social sciences; Anthropology; Cognitive psychology; Cognitive Psychology; Anthropology; Social Sciences, general